Influence Of Marketing Automation on Customer Retention - Kanmani J, Kanmani J; M. Kavitha, M. Kavitha; T. Prabaharan, T. Prabaharan (Journal of Neonatal Surgery, 2025)
Automating email campaigns, including sending personalized emails, newsletters, and promotional offers. It create email workflows that cater to customers based on real-time triggers, specific behaviors, and timelines. Automating tasks like sending welcome emails, follow-up emails, and cart abandonment reminders frees up time for other marketing efforts. Automation tools help present timely upsell and cross-sell offers by analyzing past behavior and predicting future needs. The important factors that influence customers on marketing automation are Social Media Management, Lead Generation, Lead Nurturing, Lead Scoring, Personalized Content. Finally, it concludes that personalized content developed through automation marketing leads to customer retention..